Determinasi Efektivitas Deteksi dan Pencegahan Fraud: Kajian Sistematis Multilevel Terintegrasi - Aan Andrianingsih; Abdul Rohman (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose - This study aims to synthesize academic literature on the determinants of effective fraud detection and prevention across multilevel dimensions. Method - A Systematic Literature Review (SLR) was conducted using 34 peer-reviewed articles from the Scopus database published between 2016 and 2025. The study applied the PICO strategy and thematic synthesis across three systemic levels: technology, organization, and individual. Main Findings - This study finds that anti-fraud effectiveness relies on the synergy of technology, organizational governance, and individual factors. The literature remains fragmented and geographically biased. The lack of longitudinal research is also a key limitation. Theory and Practical Implications - This research emphasizes the importance of integrative and multilevel approaches to designing effective fraud risk management systems. It offers practical guidance for policymakers to combine technological innovation with strengthened governance and individual ethics. Novelty - This study proposes a unified conceptual framework integrating technological, organizational, and individual determinants into a coherent fraud risk management system.